Membangun Budaya Literasi Mahasiswa Pascapandemi melalui Optimalisasi Perpustakaan: Studi Kasus pada Perpustakaan STT Intheos Surakarta - kangmasRifai; Pebrina Dwi Sari; Ayub E Lande3 (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2023)
AbstractThe Covid 19 pandemic, entering its third year, has brought many changes in all fields, includingactivities in the campus library. Libraries can no longer fully carry out complete face-to-faceservices, but various restrictions have been placed on reducing mobility and suppressing thetransmission of the COVID-19 virus. Therefore, it is urgent for the recovery of the library after thepandemic, namely by optimizing the campus library so that library services can be felt again by thecampus students. In addition, to re-earth the literacy culture and student interest in reading whichhas decreased due to the pandemic. Because one of the benchmarks for competent students in the21st century is students who think critically, have global insight, and have high character andspiritualism. This study uses a descriptive qualitative research method with a case study approachthat is focused on students of STT Intheos Surakarta and the efforts made by the campus library tooptimize the library, including launching a campus literacy movement, socializing the program,creating a lecture reading corner, increasing the competence of librarians in digital libraries,digitizing theology books, maximizing social media as a means of promoting new book catalogs andimproving modern library supporting infrastructure